Research and Development of Supramolecules as Anticancer Drugs - Manjit; Mishra B. (My University, 2025)
Cancer has a significant effect on society across the globe, specifically in the United States, which has the highest mortality rate. According to the National Cancer Institute, new cancer es in the United States are expected to exceed 1,918,030 in 2022, with 609,360 fatalities. Despite the fact that several novel drugs have been identified, their in vivo efficacy is restricted due to their extremely lipophilic nature. Furthermore, anticancer drugs have severe toxic or adverse effects on normal cells or tissues. As a result, the quest for a safe and reliable drug entity is essential in order to enhance the drug bioavailability and avoid deleterious effects on normal cells. The supramolecular assembly can be considered such a novel anticancer drug entity to efficiently deliver the drugs with minimal side effects and maximal therapeutic efficacy. Supramolecules can include a variety of nanostructures, layer-by-layer assemblies, conjugates, etc. and offer a high quantitative drug loading and therapeutic release in established carrier degradation and clearance pathways. The modularity of supramolecules also makes it possible to integrate several drugs in a single platform for improved therapeutics outcomes. Supramolecules have tuneable size and shape, which may increase blood circulation, translocation and system efficacy. This chapter will provide a comprehensive insight into the development of various types of supramolecules for cancer therapy, their role in improving the performance of the therapy and regulatory status. Furthermore, the chapter will also shed a light on various targeting strategies that can facilitate the improved translation of supramolecules as anticancer drugs. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2022.